Digital Marketing Transformation in Increasing Fundraising at Islamic Philanthropic Institutions - Afandi, Ahmad; Amalia, Alfi; Amsari, Syahrul (LifeSciFi, 2025)
The use of digital marketing in Islamic philanthropic institutions, especially for the collection of Zakat, Infaq, and Shodaqoh (ZIS) funds, is a strategic innovation that increases the effectiveness of fundraising. This study using qualitative descriptive methods, data were obtained through observation, interviews, and digital media analysis. The Organisation utilizes various digital platforms such as websites, social media (Instagram, Facebook), and QR codes as the main tools for fundraising. The strategies implemented include the use of storytelling, educational content, and transparent financial reporting, which have been proven to significantly increase community involvement. The results of the study showed an increase in the number of donors by up to 40% and a change in donation behaviour, with more people choosing to donate online and regularly. However, challenges remain, such as limited digital marketing expertise, limited budget, and public scepticism towards the transparency of zakat funds. From an Islamic economic perspective, strategy is in line with sharia principles such as transparency, justice, and welfare. The study recommends increasing digital capacity, collaborating with Muslim influencers, and strengthening public trust through strong narratives and open reporting. A sustainable and sharia-compliant digital strategy can increase fundraising and wider social impact in society.